How Does Agro-Tourism Integration Influence the Rebound Effect of China’s Agricultural Eco-Efficiency? An Economic Development Perspective - Jiang, Guirong (Frontiers in Environmental Science, 2022)
Agro-tourism integration is a breakthrough to flourish rural industries and fulfill rural revitalization. Also, agricultural eco-efficiency and agro-tourism integration are closely linked, so investigating the relationship between the two is significant for realizing high-quality agro-ecological development in China. However, existing studies have ignored the impact of agro-tourism integration on agricultural eco-efficiency. For this purpose, using a dataset of 30 provincial administrative regions in China from 2001 to 2019, this paper employs the Entropy weight approach and super efficient Slack-Based Measure (SBM) approach to measure the agro-tourism integration level and agricultural eco-efficiency, respectively. The system Generalized Method of Moments (SYS-GMM) approach is applied to investigate the effect of agro-tourism integration on agricultural eco-efficiency. The statistical results reveal that agro-tourism integration significantly contributes to agricultural eco-efficiency, which remains valid after the robustness checks are executed. There is also significant path-dependence of agro-tourism integration. Finally, agro-tourism integration significantly contributes to agricultural eco-efficiency in the eastern region, while it significantly inhibits agricultural eco-efficiency in the central-western region. Our findings suggest that policymakers not only reinforced the deep integration of agriculture and tourism to stimulate the overall rural revitalization, but also formulated agro-tourism integration policies in a differentiated and green manner to contribute to agricultural eco-efficiency growth.